Simulations of surface and bulk acoustic wave MEMS biosensors - Jamil, Nadira; Nordin, Anis Nurashikin; Voiculescu, Ioana; Mel, Maizirwan (2010)
Traditionally a telecommunication device, the emerging application of acoustic wave devices as sensors is rapidly gaining attention due to its high sensitivities. In this work, a comparative study of surface (SAW) and bulk (BAW) acoustic wave biosensors is presented. The MEMS SAW resonator is formed using a lithium niobate substrate with Al electrodes while the BAW resonator is formed using quartz substrate with gold electrodes. Finite element simulations of a 290 MHz SAW and a 220 MHz BAW resonator were performed using COMSOL Multiphysics #x2122;. Both models were simulated to determine their resonance frequency and frequency shift due to the loading of DF-1 animal cells, a biological material. The structure of the SAW device allows an additional transient simulation, which provides information regarding the acoustic wave propagation delay due to the presence of the cells. From the simulations it was observed that the SAW device yielded 2.8 MHz frequency shift ( #x0394;f) due to the cells while the BAW device provided #x0394;f of 2.7 MHz. The propagation delay in the SAW resonator due to the cells was simulated to be 3.5 ns.